Szkoda środowiskowa i jej ubezpieczenie - Panasiewicz, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Business is still developing with the aspiration to get more and more benefits which can create a number of new impediments - particularly those which are unknown till now. They can cause different damages not only in the field of the people activity but also in the personal and financial area. That is why new instruments are implemented in all environment area in the whole world. Among those instruments the most popular is the environmental insurance. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 78-86